2016
DOI: 10.1111/1468-0106.12155
|View full text |Cite
|
Sign up to set email alerts
|

Using Weighted Shapley Values to Measure the Systemic Risk of Interconnected Banks

Abstract: A macro‐prudential approach to financial regulation should reasonably evaluate the systemic risk of individual institutions. We introduce a measure of the systemic risk of interconnected banks using the weighted Shapley value, which characterizes banks' systemic risk by capturing two characteristics: (i) a bank's risk exposure of the primitive asset structure; and (ii) its position in the interbank network. An empirical implementation reveals that the primitive asset structure and interbank connections are mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…(2015), the Kenyan IMM by Fan et al. (2018), the Chinese banking system by Lin (2018), the European payment system TARGET2 by Gabrieli and Salakhova (2019), and the Austrian IMM network by Diem et al. (2020) all confirmed that systemic risk positively depends on the level of interconnectedness in the interbank network.…”
Section: Results Of Integrative Review: the Affecting Factorsmentioning
confidence: 85%
See 3 more Smart Citations
“…(2015), the Kenyan IMM by Fan et al. (2018), the Chinese banking system by Lin (2018), the European payment system TARGET2 by Gabrieli and Salakhova (2019), and the Austrian IMM network by Diem et al. (2020) all confirmed that systemic risk positively depends on the level of interconnectedness in the interbank network.…”
Section: Results Of Integrative Review: the Affecting Factorsmentioning
confidence: 85%
“…There is an idea that an interconnected bank’s systemic risk depends not only on the expected loss it imposes directly on depositors but also on its position in the IMM network (Lin, 2018; Puhr et al., 2012). Accordingly, the first defaulted node’s central position in the network is the next frequent attribute that affects the systemic risk.…”
Section: Results Of Integrative Review: the Affecting Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The next example shows how the a priori Shapley value can be applied to a financial system of banks (see, e.g., Allen and Gale (2000), Battiston et al(2012), Lin (2016)) in order to measure the contribution of each bank to systemic risk. The risk measure function h is given by:…”
Section: Some Illustrative Examplesmentioning
confidence: 99%